Efficiency of using a new generation feed additive for dairy cows in the North - Nikolaeva N.A.; Borisova P.P.; Alekseeva N.M.; Batyushkin V.D.; Zakharova L.N. (Ветеринария и кормление)
Research work to evaluate the effectiveness of using a feed additive in the form of a bolus was carried out in the conditions of the livestock complex of Horobut LLC in the Megino-Kangalassky ulus of the Republic of Sakha (Yakutia). The duration of the scientific and economic experiment was 281 days: from January 16 to October 23, 2023. The diet of dairy cows consisted of 10.0 kg of mixed-grass hay, 16.0 kg of silage and 2.0 kg of feed. Cows in the experimental group with a farm diet received the feed additive "Calcitop bolus" at a dose of 1 bolus per head once during lactation. In the studied diets, the ratio of metabolic energy to dry matter was 8.30 with a norm of 8.57, digestible protein to metabolic energy was 7.86 with a norm of 8.10. In terms of milk yield, the experimental group of cows that received a mineral and vitamin supplement in their diet turned out to be more economically effective, so milk productivity for 281 days of lactation amounted to 2725.7 kg, while more milk was obtained than from analogues of control cows by 204.3 kg or by 8.1% (**P<0.99). The high milk yield was 573.1 kg and was higher by 31.1 kg, respectively. The consumption of concentrates per 1 kg of milk was 206.2 g and reduced the consumption of concentrates for the production of 1 kg of milk compared to the control by 8.97%. Calculation of the economic efficiency of milk production showed that the cost of producing 1 quintal of milk from cows in the experimental group was 82.0 rubles lower than in the control group. At the same time, profit from the sale of milk increased by 26.8%, the level of profitability of milk production amounted to 7.8%. All indicators characterizing the biological value of milk fluctuated slightly and corresponded to the indicators of high-quality natural milk. Therefore, the use of the feed additive "Calcitop Bolus" for Simmental cows made it possible to balance the diets in terms of missing nutrients.